A Comparative Systematic Literature Review and Bibliometric Analysis on Sustainability of Renewable Energy Sources - Jabeen, Samrena; Malik, Subha; Khan, Soha; Khan, Nohman; Qureshi, Muhammad Imran; Saad, Mohd Shamsuri Md (International Journal of Energy Economics and Policy, 2020)
The rapid growth of the human population of the planet has led to mounting energy demands; conventional sources of energies are not enough to fulfil the energy demand. Therefore, the search for alternative sources has become the most profuse challenge. Presently, many alternatives are being studied and implemented in literature—the renewable sources which are less harmful and environmentally acceptable for future generations. The current study aims to review the renewable resources which are highly examined in the last decade by the researcher. For this purpose, two databases, web of science and Scopus, are selected to extract the data. The data selection and rejection process are following the PRISMA statement that is an authentic eligibility criterion using by researchers. After a detailed function, the final fifty-two studies are selecting for the current review. The classification of data is mainly discussing biofuels, solar energy, wind energy, and renewable electricity. Literature is also showing that fossil fuels are environmentally very harmful, and developed countries are significantly replacing the renewable energies source. Bibliometric results are showing that research collaborations are exceptionally done in U.S. and European countries. The findings of the current study are a novel concept to evaluate and review the published literature on renewable energies in the last decade. Keywords: Bibliometric Analysis, Sustainability, Renewable Energy Sources JEL Classifications: P28, Q42, Q47 DOI: https://doi.org/10.32479/ijeep.10759